ANALISIS BENTUK STEREOTIP MASKULINITAS PADA VISUAL TOKOH UTAMA LAKI-LAKI DALAM BUKU CERITA ANAK TERBITAN LET’S READ! INDONESIA - Kaira Sulasmoro; Riama Maslan Sihombing (Wimba : Jurnal Komunikasi Visual, 2023)
Gender discrimination in the form of stereotyping towards males is an issue that is often overlooked. In order to meet the demands of being a “real man”, men are often generalized into stereotypes such as: acting rough, aggressive, forbidden to show weakness, and are expected to do jobs and activities that rely more on physical strength and exist in public spaces. Let’s Read! Indonesia is an organization from Asia with a digital library for children that is able to address heavy issues such as gender equality, providing a platform for children to learn while also being a means to reconstruct masculine stereotypes from an early age. This research aims to analyse the visual representation of male main characters in Let’s Read! Indonesia’s books and determine whether these depictions embody masculine stereotypes or not. The characters’ visuals were analysed using the ideational metafunction, which examines their characteristic form (expression, attitude, and appearance), activities, and the activity space. From the five books that were examined, three of the main characters were found to exhibit masculine stereotypes, while the other two exhibited conflicting characteristics towards masculine stereotypes.